Menyingkap Karakteristik Penalaran Matematis Siswa dalam Pemecahan Masalah Geometri Ruang : Tinjauan Berdasarkan Kategori Kemampuan Matematika - Budi Lestari, Andika Setyo; Arifah, Siti (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to analyze students' mathematical reasoning in solving problems related to flat-walled three-dimensional shapes, examined through the lens of their mathematical proficiency levels. Design/methodology/approach: The research employs a qualitative descriptive approach. Data were gathered through assessments and interviews conducted with three subjects representing high, moderate, and low mathematical abilities. Findings: The results indicate that robust mastery of material correlates positively with effective reasoning, as evidenced by the high-ability subject meeting all reasoning indicators. Conversely, subjects with moderate and low abilities experienced significant difficulties due to a deficit in basic conceptual understanding, thereby limiting their capacity to identify procedural steps, integrate concepts, and construct coherent arguments. Practical implications: These findings serve as a reference for developing adaptive mathematics learning strategies oriented toward conceptual comprehension to mitigate the tendency of students merely memorizing formulas. Originality/value: This research contributes a profound overview of reasoning characteristics across various ability levels, specifically within the context of flat-walled geometry, to foster logical and systematic thinking skills. Purpose: Penelitian ini bertujuan menganalisis penalaran matematika siswa dalam menyelesaikan soal bangun ruang sisi datar, ditinjau berdasarkan kemampuan matematika siswa. Design/methodology/approach: Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui tes dan wawancara kepada tiga subjek dengan tingkat kemampuan tinggi, sedang, dan rendah. Findings: Hasil menunjukkan bahwa penguasaan materi yang kuat berkorelasi positif dengan penalaran efektif, di mana subjek berkemampuan tinggi menguasai semua indikator penalaran. Sebaliknya, subjek berkemampuan sedang dan rendah mengalami kesulitan signifikan akibat defisit pemahaman konsep dasar, yang membatasi kemampuan mereka dalam mengidentifikasi langkah, mengintegrasikan konsep, dan menyusun argumen. Practical implications: Hasil ini menjadi acuan untuk pengembangan pembelajaran matematika yang adaptif dan berorientasi pada pemahaman konseptual untuk mengatasi kecenderungan siswa yang hanya menghafalkan rumus. Originality/value: Kontribusi penelitian ini memberikan gambaran mendalam tentang karakteristik penalaran pada berbagai tingkat kemampuan dalam materi bangun ruang sisi datar guna mendukung kemampuan berpikir logis dan sistematis.